Advances in high moisture extrusion cooking for meat analogue with 3D and 4D printing approaches: a comprehensive review - Prostuti Chakravorty; Amit Baran Das (Discover Food)
Abstract The escalating issue of global warming is closely linked to greenhouse gas emissions resulting from agricultural practices and land use, which together account for roughly 23% of global emissions. Among these, livestock production is a major contributor, responsible for 12% to 18% of emissions, highlighting its environmental impact. Despite providing essential nutrients such as proteins and vitamins, meat production exacerbates greenhouse gas emissions and poses significant challenges related to water use and pollution. Therefore, a sustainable and healthful substitute for animal meat must be the main priority due to environmental and health considerations namely obesity, high blood pressure and cardiovascular disease. The texture, appearance, and mouthfeel of animal flesh can be mimicked by meat substitutes made of plant proteins. This highlights the importance of exploring innovative approaches to develop alternatives to traditional meat products. This article gives a thorough review of high-moisture extruded meat alternatives made with cutting-edge 3D and 4D printing technologies. The article reviews the latest developments in meat analogues constitution through high moisture extrusion and 3D printing techniques and also discusses the possibility of implementing of 4D printing for the same. While extrusion remains a key method for producing these substitutes, with a control over the key parameters such as nozzle diameter, layer height and temperature, 3D and 4D printing offer exciting opportunities to overcome existing limitations concerning nutritional value and advance the field. The development of plant-based meat alternatives holds significant promise for transforming the food industry and promoting a more sustainable future.